Assessment of a service-learning project to work on professional competences: Experience between students of Psychology and students with intellectual disabilities - Silva Lorente, Isabel; Escribano Barreno, Cristina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
University currently pursues a comprehensive education of the students. This Service-Learning project presents an inclusive educational experience with students of the Degree in Psychology and students with intellectual disabilities in training for their preparation for the labor market through a simulation of a job interview. The experience shows diverse academic and social learning carried out by both groups, highlighting a greater knowledge of the characteristics and capacities of people with intellectual disabilities. As for the recipients, the need to improve expression in future job interviews is detected, and as for the project, the need to bet on more lasting projects.